An Important Stage in the Development Process of the “Patient Safety Education Program”: Needs Assessment (A Qualitative Study) - Tuba Ötün; Emine Akçin Şenyuva (Sağlık Bilimleri Üniversitesi Hemşirelik Dergisi)
Introduction: It is important to recognize the needs of nurses in order to develop their knowledge and skills about patient safety and to create an education program.Aim: The study aims to recognize the needs of nurses in order to form a basis for structuring the “Patient Safety Education Program” based on the Constructivist Learning Model.Method: The study is designed as a qualitative study. The participants were randomly reached. The data were collected by using a semi-structured interview form.Results: The results of the study show that nurses are intertwined with patient safety in all fields of care. When structuring education programs related to patient safety, it is necessary to select subjects, teaching methods, materials, and assessment methods that will improve nurses' knowledge and skills related to patient safety.Conclusion: In accordance with these results, it can be recommended to use the study results when structuring formal educational programs.